Do surau strategies go beyond modern schooling? a qualitative study on efforts to sustain existence and strengthen community education - Suhaimi Suhaimi; Arwan Arwan; Miftahuddin Miftahuddin; Darmawati Darmawati; Syarifah Syarifah; M. Fahli Zatrahadi; Rahmad Rahmad; Meylani Fitria (Jurnal Konseling dan Pendidikan, 2025)
This research aims to reveal the management strategy of surau as a traditional Islamic educational institution that still exists and is even able to surpass modern Islamic schools in various dimensions of educational management. Using a descriptive qualitative approach and field research method, this research was conducted in three representative locations in Kampar Regency Bangkinang (urban), Gadang Island (border area), and Simalinyang (rural). The data was obtained through in-depth interviews, participatory observations, and document analysis involving ustaz, community leaders (ninik mamak), and village government officials as the main sources. Data analysis is phenomenologically conducted through the process of reduction, categorization, and interpretation of social significance to find a form of strategy for managing surau amid the current modernization of Islamic education. Research results show that surau has eight main strategies that are its managerial advantages. First, the emotional and social closeness between the management of the surau and the community that strengthens the sense of belonging and collective trust. Second, the flexibility of the management and learning system that allows adjustment to the social and economic needs of the community. Third, the integration of local spiritual, social, and cultural values into all educational activities. Fourth, accessibility and affordable education costs, make the surau inclusive for all levels of society. Fifth, an active role in the formation of the character and spirituality of students through exemplary practice and worship habitation. Sixth, the ability to adapt to modernization, including the use of digital media and simple administrative systems. Seventh, people's collective participation in institutional management, which strengthens the social and economic sustainability of the surau. Eighth, the charismatic and transformational leadership of my lords and ustaz, who inspired and encouraged the community to achieve common goals. The results of this study confirm that the power of surau lies in the ability to combine traditional values with modern management practices, forming relevant, adaptive, and community-based hybrid management models. With this strategy, surau is able to offer more humanistic, inclusive, and contextual Islamic education alternatives than modern formal educational institutions. These findings contribute conceptually to the development of value-based and community-based Islamic education management in the face of the challenges of globalization.